2023
DOI: 10.30892/gtg.49329-1113
|View full text |Cite
|
Sign up to set email alerts
|

Current Issues of Health and Wellness Tourism Based on Population Health Preservation in Eastern Kazakhstan

Shynar SHYNGYSBAEVA,
Abdimazhit SAIPOV,
Ardak ALDASHEVA
et al.

Abstract: Research is aimed at elucidating the salient challenges impeding the maturation of the health and wellness tourism cluster within the Eastern Kazakhstan region. The inquiry encompasses findings from a customer survey conducted within the Eastern Kazakhstan Region's sanatorium resort visitors in Katon-Karagay District in 2022-2023. Significant attention is devoted to the natural-ecological, economic-infrastructure, and socio-cultural components constituting the tourist cluster are expounded upon. Quantitative a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Research in various countries and resorts (Poland, Spain, Croatia, China, and Kazakhstan) has shown that customer expectations and, consequently, business performance are strongly dependent on the diversity and performance of medical and wellness facilities [107,108], the number and involvement of qualified medical staff [109], and medical procedures and entertainment programs [110,111]. Finally, other studies focus on finding a business model for health and spa tourism companies that reconciles the expectations of tourists and stakeholders with environmental and sustainability imperatives under conditions of efficiency and long-term profitability [112].…”
Section: General Contextmentioning
confidence: 99%
“…Research in various countries and resorts (Poland, Spain, Croatia, China, and Kazakhstan) has shown that customer expectations and, consequently, business performance are strongly dependent on the diversity and performance of medical and wellness facilities [107,108], the number and involvement of qualified medical staff [109], and medical procedures and entertainment programs [110,111]. Finally, other studies focus on finding a business model for health and spa tourism companies that reconciles the expectations of tourists and stakeholders with environmental and sustainability imperatives under conditions of efficiency and long-term profitability [112].…”
Section: General Contextmentioning
confidence: 99%